NEWS OF THE NATIONAL IMMUNIZATION SCHEDULE - O. V. Shamsheva; I. E. Koltunov (Детские инфекции (Москва))
The article presents the changes Immunization Schedule Russia introduced in 2014. In new Schedule now is the vaccination against pneumococcal disease for all children of 2 months with revaccination at 4 and 15 months old; excluded from the Schedule second revaccination against tuberculosis. At risk groups to be vaccinated against the flu, entered pregnant women and persons subject to military conscription. Recommendations on use of vaccines containing relevant antigens for the Russian Federation, to provide maximum effectiveness of immunization and vaccines that do not contain preservatives in children under 1 year of age. Offered to create a council of experts in the field of vaccinology and vaccine prevention